Processes Occurring within the Biofilm - Tolnai, Béla (Periodica Polytechnica Civil Engineering, 2024)
Biological filtration is a complex process consisting of two consecutive stages. The nutrient transport stage, which is influenced by various fluid mechanical and surface-physical factors, represents a precondition for the biochemical process taking place within the biofilm. Biological water filtration is based on the catalyzed decomposition of contaminant molecules with the help of enzymes. This article, in addition to describing the conditions and mode of action typical within this second stage, also aims to explore the practical implications of the established results, including the controllability of biological reactors.